2R-Regeneration of an RZ-DPSK Signal Using a Nonlinear Amplifying Loop Mirror - Cvecek, K; Sponsel, K; Onishchukov, G; Schmauß, Bernhard; Leuchs, Gerd (IEEE Photonics Technology Letters, 2007)
The performance of a nonlinear amplifying loop mirror as a 2R-regenerator for return-to-zero differential-phase-shift-keyed signals has been investigated experimentally. The measured power characteristics and phase functions show that the signal amplitude is regenerated while the signal phase is preserved in the setup. A significant eye-opening improvement and a negative power penalty of about 1.5 dB were obtain
lhft_intern.bib::cvecek07